Re-imagining Bengal : architecture, built environment and cultural heritage - Ahmed, K. Iftekhar; Habib, Mohammad (Sahibabad, Dist. Ghaziabad : Copal Publishing Group, 2018)
Contributed articles on ancient architecture and state of historic Bengal buildings and their designs.
Includes architectural renderings.
Includes bibliographical references.
ARC
Trim Education
Keywords: Architecture, Ancient -- India -- Bengal; Historic buildings -- India -- Bengal -- Designs and plans; Architecture